Features of the alpha-cell population organization in pancreas of spontaneously hypertensive rats (SHR) - T. V. Abramova; Yu. M. Kolesnyk (Patologìâ)
Alpha cells of pancreatic islets constitute the second largest population of pancreatic endocrinocytes, and the glucagon synthesized in them plays an important role in the regulation of glucose homeostasis. At the same time, glucagon-suppressive therapy is defined as the strategically main source of success of therapy for patients with type 2 diabetes mellitus. In clinical practice, diabetes is often associated with hypertension in the metabolic syndrome, which causes interest in the pathophysiology of α-endocrinocytes.